A Testis-Specific Long Non-Coding RNA, lncRNA-Tcam1, Regulates Immune-Related Genes in Mouse Male Germ Cells - Kurihara, Misuzu; Otsuka, Kai; Matsubara, Shin; Shiraishi, Akira; Satake, Honoo; Kimura, Atsushi P. (Frontiers in Endocrinology, 2017)
Spermatogenesis is precisely controlled by hormones from the hypothalamus-pituitary-gonadal axis and testis-specific genes, but the regulatory mechanism is not fully understood. Recently, a large number of long noncoding RNAs (lncRNAs) are found to be transcribed at each stage of meiosis of male germ cells, and their functions in spermatogenesis have yet to be fully investigated. lncRNA-Tcam1 is a nuclear lncRNA which is specifically expressed in mouse male germ cells and presumed to play a role in gene regulation during meiosis. Here, we present the identification of potential target genes of lncRNA-Tcam1 using spermatocyte-derived GC-2spd(ts) cells. Initially, 55 target gene candidates were detected by RNA-sequencing of two GC-2spd(ts) cell clones that were stably transfected with transgenes to express lncRNA-Tcam1 at different levels. Expression of 21 genes of the candidates were found to be correlated with lncRNA-Tcam1 at 7-14 postnatal days, when lncRNA-Tcam1 expression was elevated. Subsequently, we examined expression levels of the 21 genes in other two GC-2spd(ts) clones, and 11 genes exhibited the correlation with lncRNA-Tcam1. Induction of lncRNA-Tcam1 transcription using the Tet-off system verified that 6 genes, Trim30a, Ifit3, Tgtp2, Ifi47, Oas1g, and Gbp3, were up-regulated in GC-2spd(ts) cells, indicating that lncRNA-Tcam1 is responsible for the regulation of gene expression of the 6 genes. In addition, 5 of the 6 genes, namely, Ifit3, Tgtp2, Ifi47, Oas1g, and Gbp3, are immune response genes, and Trim30a is a negative regulator of immune response. Altogether, the present study suggests that lncRNA-Tcam1 is responsible for gene regulation for the immune response during spermatogenesis.